Contribution of Rare and Low-Frequency Variants to Multiple Sclerosis Susceptibility in the Italian Continental Population - Clarelli, Ferdinando; Barizzone, Nadia; Mangano, Eleonora; Zuccalà, Miriam; Basagni, Chiara; Anand, Santosh; Sorosina, Melissa; Mascia, Elisabetta; Santoro, Silvia; , PROGEMUS; , PROGRESSO; Guerini, Franca Rosa; et al. (Frontiers in Genetics, 2022)
Genome-wide association studies identified over 200 risk loci for Multiple Sclerosis (MS) focusing on common variants, which account for about 50% of disease heritability. The goal of this study was to investigate whether low-frequency and rare functional variants, located in MS established associated loci, may contribute to disease risk in an ancestrally homogeneous population, testing their cumulative effect (burden) with gene-wise tests. We sequenced 98 genes in 588 Italian patients with MS and 408 and matched healthy controls (HC). Variants were selected using different filtering criteria based on allelic frequency and in-silico functional impact. Genes showing a significant burden (n=17), were sequenced in an independent cohort of 504 MS and 504 HC. The highest signal in both cohorts was observed for the disruptive variants (stop-gain, stop-loss or splicing variants) located in EFCAB13, a gene coding for a protein of unknown function (p<10-4). Among these variants, the minor allele of a stop-gain variant showed a significantly higher frequency in MS vs HC in both sequenced cohorts (p=0.0093 and p=00025), confirmed by a meta-analysis on a third independent cohort of 1298 MS and 1430 HC (p=0.001) assayed with SNP array. Real time PCR on 14 heterozygous individuals for this variant did not evidence the presence of the stop-gain allele, suggesting a transcript degradation by non-sense mediated decay, supported by the evidence that the carriers of stop-gain variant had a lower expression of this gene (p=0.0184). In conclusion, we identified a novel low-frequency functional variant associated with MS susceptibility, suggesting the possible role of rare/ low-frequency variants in MS as reported for other complex diseases.